2023
DOI: 10.3389/fnagi.2023.1261026
|View full text |Cite|
|
Sign up to set email alerts
|

The neutrophil-to-lymphocyte ratio is associated with mild cognitive impairment in community-dwelling older women aged over 70 years: a population-based cross-sectional study

Shengjie Li,
Xiaoyu Chen,
Mengze Gao
et al.

Abstract: BackgroundThe neutrophil-to-lymphocyte ratio (NLR) is a marker of inflammation that can be obtained quickly, conveniently, and cheaply from blood samples. However, there is no research to explore the effects of sex and age on the relationship between the NLR and mild cognitive impairment (MCI) in community-dwelling older adults.MethodsA total of 3,126 individuals aged over 60 years in Shanghai were recruited for face-to-face interviews, and blood samples were collected. MCI was assessed by the Mini-Mental Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…The neutrophil-to-lymphocyte ratio(NLR) was a biomarker with simple numerical values, and previous studies have shown that it was a good counting indicator in response to systemic in ammation [10].Recently, several studies have shown a positive association between elevated NLR and cognitive impairment / mild cognitive impairment [11].The results of a cross-sectional study based on 3169 people over 60 years old showed that compared with men,Female patients with MCI had signi cantly higher NLR than cognitively normal.In addition, the study also found that elevated NLR in women over 70 years old was signi cantly associated with the risk of mild cognitive dysfunction [12].NLR in the acute ischemic stroke was independently associated with PSCI after 3 months,While high NLR was speci cally associated with cognitive dysfunction in the memory and visuospatial domains [13].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The neutrophil-to-lymphocyte ratio(NLR) was a biomarker with simple numerical values, and previous studies have shown that it was a good counting indicator in response to systemic in ammation [10].Recently, several studies have shown a positive association between elevated NLR and cognitive impairment / mild cognitive impairment [11].The results of a cross-sectional study based on 3169 people over 60 years old showed that compared with men,Female patients with MCI had signi cantly higher NLR than cognitively normal.In addition, the study also found that elevated NLR in women over 70 years old was signi cantly associated with the risk of mild cognitive dysfunction [12].NLR in the acute ischemic stroke was independently associated with PSCI after 3 months,While high NLR was speci cally associated with cognitive dysfunction in the memory and visuospatial domains [13].…”
Section: Introductionmentioning
confidence: 69%
“…Higher NLR was associated with cognitive decline and dementia [11,12].A large number of studies have shown that high NLR can be found in cognitive dysfunction after acute ischemic stroke [13], The increase of NLR may represented a high level of in ammation, which promoted the occurrence and development of cognitive decline after cerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%